A Combination of Lipoic Acid Plus Coenzyme Q10 Induces PGC1α, a Master Switch of Energy Metabolism, Improves Stress Response, and Increases Cellular Glutathione Levels in Cultured C2C12 Skeletal Muscle Cells. (9th May 2012) - Wagner, A. E.; Ernst, I. M. A.; Birringer, M.; Sancak, Ö.; Barella, L.; Rimbach, G.
Abstract : Skeletal muscle function largely depend on intact energy metabolism, stress response, and antioxidant defense mechanisms. In this study, we tested the effect of a combined supplementation of α -lipoic acid (LA) plus coenzyme Q10 (Q10) on PPAR γ -coactivator α (PGC1 α ) activity, expression of glutathione-related phase II enzymes and glutathione (GSH) levels in cultured C2C12 myotubes. Supplementation of myotubes with 250  μ mol/L LA plus 100  μ mol/L Q10 significantly increased nuclear levels of PGC1 α, a master switch of energy metabolism and mitochondrial biogenesis. The increase of nuclear PGC1 α was accompanied by an increase in PPAR γ transactivation, a downstream target of PGC1 α, and an increase in mitochondrial transcription factor A mRNA centrally involved in mitochondrial replication and transcription. Furthermore, supplementation of myotubes with LA plus Q10 resulted in an increase of genes encoding proteins involved in stress response, GSH synthesis, and its recycling. In LA-plus-Q10-treated myotubes a significant 4-fold increase in GSH was evident. This increase in GSH was accompanied by increased nuclear Nrf2 protein levels, partly regulating γ GCS and GST gene expression. Present data suggest that the combined supplementation of skeletal muscle cells with LA plus Q10 may improve energy homeostasis, stress response, and antioxidant defense mechanisms.